Fetal Cholelithiasis: Antenatal Diagnosis and Neonatal Follow-Up in a Case of Twin Pregnancy – A Case Report and Review of the Literature - Hurni, Yannick; Vigo, Francesco; von Wattenwyl, Begoña Lipp; Ochsenbein, Nicole; Canonica, Claudia (Ultrasound International Open, 2017)
Fetal cholelithiasis is a rare finding during a third-trimester ultrasound with an average incidence rate of 0.07–1.15%. We report a case of fetal cholelithiasis in twins, observed in a patient with monochorionic diamniotic twin pregnancy hospitalized at our unit for signs of premature labor. We present the outcome of the 2 neonates with a clinical and sonographic follow-up. In addition, we offer a comprehensive review of the literature available to date.
Keywords: fetal cholelithiasis; fetal gallstones; intrahepatic cholestasis of pregnancy